(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the smoking status among students at Phenikaa University in 2024 and the associated factors. Methods: A cross-sectional study was conducted on 1045 students at Phenikaa University, from September to December 2024. Data were collected via an online survey using a pre-designed Google Forms questionnaire. Results: The prevalence of smoking among students was 6.7%. Smoking status was statistically significantly associated with geographical origin, academic discipline, year of study, family history of smoking, and peer smoking (p < 0.05). Recommendations: It is recommended to enhance parental and peer awareness of the detrimental effects of smoking, thereby encouraging their active participation in the prevention and reduction of smoking among students.